Phylogenetic relationships of rock-inhabiting black fungi belonging to the widespread genera Lichenothelia and Saxomyces. (2nd January 2019) - Ametrano, Claudio G.; Knudsen, Kerry; Kocourková, Jana; Grube, Martin; Selbmann, Laura; Muggia, Lucia
ABSTRACT: Rock-inhabiting fungi (RIF) are adapted to thrive in oligotrophic environments and to survive under conditions of abiotic stress. Under these circumstances, they form biocoenoses with other tolerant organisms, such as lichens, or with less specific phototrophic consortia of aerial algae or cyanobacteria. RIF are phylogenetically diverse, and their plastic morphological characters hamper the straightforward species delimitation of many taxa. Here, we present a phylogenetic study of two RIF genera, Lichenothelia and Saxomyces . Representatives of both genera inhabit rather similar niches on rocks, but their phylogenetic relationships are unknown so far. The cosmopolitan genus Lichenothelia is recognized by characters of fertile ascomata and includes species with different life strategies. In contrast, Saxomyces species were described exclusively by mycelial characters found in cultured isolates from rock samples collected at high alpine elevations. Here, we use an extended taxon sampling of Dothideomycetes to study the phylogenetic relationships of both Lichenothelia and Saxomyces . We consider environmental samples, type species, and cultured isolates of both genera and demonstrate their paraphyly, as well as the occurrence of teleomorphs in Saxomyces . We applied three species delimitation methods to improve species recognition based on molecular data. We show the distinctiveness of the two main lineages of Lichenothelia (Lichenotheliales s. str.) and Saxomyces and discuss differences in species delimitation depending on molecular markers or methods. We revise the taxonomy of the two genera and describe three new taxa, Lichenothelia papilliformis, L. muriformis, and Saxomyces americanus, and the teleomorph of S. penninicus .